Life-long microbiome rejuvenation improves intestinal barrier function and inflammaging in mice - Felix Sommer; Joana P. Bernardes; Lena Best; Nina Sommer; Jacob Hamm; Berith Messner; Víctor A. López-Agudelo; Antonella Fazio; Georgios Marinos; A. Samer Kadibalban; Go Ito; Maren Falk-Paulsen; et al. (Microbiome)
Abstract Background Alterations in the composition and function of the intestinal microbiota have been observed in organismal aging across a broad spectrum of animal phyla. Recent findings, which have been derived mostly in simple animal models, have even established a causal relationship between age-related microbial shifts and lifespan, suggesting microbiota-directed interventions as a potential tool to decelerate aging processes. To test whether a life-long microbiome rejuvenation strategy could delay or even prevent aging in non-ruminant mammals, we performed recurrent fecal microbial transfer (FMT) in mice throughout life. Transfer material was either derived from 8-week-old mice (young microbiome, yMB) or from animals of the same age as the recipients (isochronic microbiome, iMB) as control. Motor coordination and strength were analyzed by rotarod and grip strength tests, intestinal barrier function by serum LAL assay, transcriptional responses by single-cell RNA sequencing, and fecal microbial community properties by 16S rRNA gene profiling and metagenomics. Results Colonization with yMB improved coordination and intestinal permeability compared to iMB. yMB encoded fewer pro-inflammatory factors and altered metabolic pathways favoring oxidative phosphorylation. Ecological interactions among bacteria in yMB were more antagonistic than in iMB implying more stable microbiome communities. Single-cell RNA sequencing analysis of intestinal mucosa revealed a salient shift of cellular phenotypes in the yMB group with markedly increased ATP synthesis and mitochondrial pathways as well as a decrease of age-dependent mesenchymal hallmark transcripts in enterocytes and TA cells, but reduced inflammatory signaling in macrophages. Conclusions Taken together, we demonstrate that life-long and repeated transfer of microbiota material from young mice improved age-related processes including coordinative ability (rotarod), intestinal permeability, and both metabolic and inflammatory profiles mainly of macrophages but also of other immune cells. Video Abstract